2015
DOI: 10.1074/jbc.m115.641092
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Initiates Epithelial to Mesenchymal Transition and Induces β-Catenin-mediated Transcription in Epithelial Ovarian Carcinoma

Abstract: Background: Aberrant activation of Wnt/␤-catenin signaling is found in ovarian cancer, even when mutations are absent. Results: The bioactive lipid lysophosphatidic acid induces ␤1-integrin clustering, nuclear ␤-catenin translocation, and activation of Tcf/Lef-regulated gene expression. Conclusion: Microenvironmental lipids modulate ␤-catenin signaling. Significance: Understanding the mechanisms of Wnt/␤-catenin activation provides a basis for therapeutic targeting of the pathway in ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 77 publications
2
35
0
Order By: Relevance
“…Conversely, dysfunctional ATX and LPA signaling is found in several cancer, where ATX is among the top 40 most up-regulated genes 42 . In literature, only two studies have associated LPA to the induction of EMT in ovarian cancer cells 48,49 . In particular, it has been reported that LPA induced the transcription of EMT-related genes through the activation of HIF1α 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, dysfunctional ATX and LPA signaling is found in several cancer, where ATX is among the top 40 most up-regulated genes 42 . In literature, only two studies have associated LPA to the induction of EMT in ovarian cancer cells 48,49 . In particular, it has been reported that LPA induced the transcription of EMT-related genes through the activation of HIF1α 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This is also the first report to our knowledge that has shown the importance of LPA-signaling via Gαi2 in inducing EMT. Although a recent study reported the ability of LPA to induce EMT via Wnt/β-catenin signaling pathways [69], the underlying mechanism was not fully clarified. In this regard, our study presented here firmly establishes the role of Gαi2-Src-HIF1α signaling nexus in promoting LPA-stimulated induction of Slug which is involved in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin activation in lung MCs was found to be regulated via LPA1-dependent GSK-3β phosphorylation. Others have since reiterated the role for LPA in promoting β-catenin stabilization and transcriptional activation (43,44). However, all these investigations have been performed in vitro, and whether LPA truly acts as a ligand in vivo had not been established.…”
Section: Methodsmentioning
confidence: 99%